INFLUENCE OF STOCKING DENSITY AND FEEDING TOFU WITH DIFFERENT FREQUENCIES GROWTH OF POPULATION SILK WORM (Tubifex sp) - Abdi Zulfan; Nuraini '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Silk worms are one type of live food favored because it has nutrients that are good for the growth of fish larvae. This study aims to determine the effect of stocking density and feeding tofu to a different frequency on the growth of silk worms. This study was conducted in 26 March to 22 May 2016 located at Jln. Kamboja No. 38, Simpang Baru, Panam, Pekanbaru. The media used in the research is a mixture of mud, dung quail, pulp, bran, sand and EM4. The material used is silk worms obtained from collectors. This research was conducted by an experimental method using a completely randomized design (CRD) factorial with 2 factors and 3 levels of treatment and repeated three times. The treatment in this treatment: P45F1: stoking density 45 g and Frequency 1x1 days, P45F2: stoking density 45 g and Frequency 1x2 days, P45F3: stoking density 45 g and Frequency 1x3 days, P55F1: stoking density 55 g and Frequency 1x1 days, P55F2 : Solid Tebar 55 g and Frequency 1x2 days, P55F3: Solid Tebar 55 g and Frequency 1x3 days, P65F1: stoking density 65 g and Frequency 1x1 days, P65F2: stoking density 65 g and Frequency 1x2 days, P65F3: stoking density 65 g and frequency 1x3 days. The data observed in the form of biomass growth, population, length growth and quality of water. The results of the study, indicating that the stocking density and feeding tofu with different frequenci es no significant effect (P> 0.05) on the growth of biomass, population and the growth of length silk worms. The highest growth of biomass was obtained in treatment P55F3 (stocking density 55g and Frequency 1x3 days) is 185.67 g / 0.098 m2. The highest the growth of length obtained in the treatment P45F1 (stocking density 45g and frequency of 1x1 days) is 1.47 cm and for growth of population is highest in treatment P55F2 (stocking density 55g and frequency of 1x2 days) is 41661.33 ind / 0.098 m2. Water quality during the research for the values of temperature, pH, Dissolved Oxygen (DO) are still in a reasonable range. Based on the results of this study concluded that the stocking density and feeding different tofu can promote the growth of silk wormsKey words: Tubifex sp., stoking density, Frequency, feses of quail., Biomass, population, the growth of length